2017
DOI: 10.1016/j.chemosphere.2017.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of urinary Benzo[a]pyrene tetrols and their relationship to other polycyclic aromatic hydrocarbon metabolites and cotinine in humans

Abstract: Biomonitoring of exposure to polycyclic aromatic hydrocarbons (PAHs) typically uses measurement of metabolites of PAHs with four or less aromatic rings, such as 1-hydroxypyrene, even though interest may be in exposure to larger and carcinogenic PAHs, such as benzo[a]pyrene (B[a]P). An improved procedure for measuring two tetrol metabolites of B[a]P has been developed. Using 2 mL urine, the method includes enzymatic deconjugation of the tetrol conjugates, liquid-liquid extraction, activated carbon solid phase e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our study supports a role for BaP in bladder carcinogenesis. BaP is a polycyclic aromatic hydrocarbon (PAH) procarcinogen found in cigarette smoke and detectable in the urine of smokers or healthy volunteers after a PAH-rich meal [8] . Cigarette smoking is the main risk factor for BLCA (estimated hazard ratio is 2–4 for current smokers [9] ).…”
mentioning
confidence: 99%
“…Our study supports a role for BaP in bladder carcinogenesis. BaP is a polycyclic aromatic hydrocarbon (PAH) procarcinogen found in cigarette smoke and detectable in the urine of smokers or healthy volunteers after a PAH-rich meal [8] . Cigarette smoking is the main risk factor for BLCA (estimated hazard ratio is 2–4 for current smokers [9] ).…”
mentioning
confidence: 99%
“…Epidemiological tests have concluded that PAHs have cancerogenic activity, e.g., contributing to lung cancer, as well as genotoxic and mutagenic activity, while BaP is a major promotor of pancreatic cancer and colorectal adenoma. Due to its affinity for fat, BaP is also detected in female milk, which puts babies at risk from the first days of their lives [ 1 , 38 , 60 , 61 ]. This is particularly important because of the influence of these chemicals on human reproductive activities.…”
Section: Discussionmentioning
confidence: 99%
“…Their presence in the human organism can lead to male infertility due to competition for aryl hydrocarbon receptors (AhRs) [ 1 , 62 ]. In women, it leads to malfunction of the ovaries, which may result in premature menopause [ 61 , 63 ]. Detailed information is provided in Table 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The urinary concentrations of BaP-r-7,t-8,t-9,c-10-tetrahydrotetrol (BPT I-1) and BaP-r-7,t-8,c-9,c-10-tetrahydrotetrol were measured in smokers and nonsmokers and results showed that the median concentration of BPT I-1 in smokers' urine (0.069 pg/mL) was significantly higher than that in nonsmokers (0.043 pg/mL). Therefore, the authors suggested that the application of BPT I-1 as a biomarker warranted further investigation (Hilton, Trinidad, Hubbard, Li, & Sjödin, 2017). In addition to metabolites, parent PAHs have also been used as biomarkers to estimate PAH exposure.…”
Section: Biomarkers Of Pah Exposurementioning
confidence: 99%